PENGARUH PEMBELAJARAN DARING (DALAM JARINGAN) TERHADAP TINGKAT KEAKTIFAN BELAJAR MAHASISWA PPKN FKIP UNIVERSITAS RIAU - Dewi, Ika Kumala; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by online learning and active learning of students of the PPKn FKIP study program, Riau University. The formulation of the problem in this study is whether there is an effect of online learning on the level of active learning of students in the PPKn FKIP study program, Riau University. This study aims to determine the effect of online learning on the level of active learning of students in the PPKn FKIP study program, Riau University. The population in this study were students from the 2018 and 2019 batches of the PPKn study program, Riau University. The sample in this study were students of the PPKn Study Program, Riau University, totaling 59 respondents and determined by purposive sampling technique. The type of research used is descriptive quantitative with the measuring tools used for each variable are questionnaires and interviews where the data obtained will be processed with the help of SPSS version 16. Based on the calculation results of SPSS version 16 of the F test, the value of Ftable Fcount, which is 68,587 4,010, thus Ho is rejected and Ha is accepted, which means online learning has an effect on student activity in the PPKn FKIP Study Program, Riau University. The coefficient of determination (R Square) is 0.546, which means that the effect of learning on student learning activities is 54.6%. While the remaining 45.4% is influenced by other variables not examined in this study. This means that the hypothesis in this study is accepted.Key Words: Influence, Online Learning, Student Learning Activities.